2022
DOI: 10.1007/s11625-022-01258-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the governance of sustainability pathways: hydraulic megaprojects, social–ecological traps, and power in networks of action situations

Abstract: To enable sustainability pathways, we need to understand how social–ecological systems (SES) respond to different governance configurations, considering their historical, institutional, political, and power conditions. We advance a robust methodological approach for the integrated analysis of those conditions in SES traps. Our advancement consists of a novel combination of the networks of action situations approach with an agency-based polycentric power typology and the concept of discursive power. We test the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 105 publications
2
7
0
Order By: Relevance
“…In other words, different local contexts can achieve transformative adaptation to one climatic hazard. These findings align with the latest interdisciplinary studies reporting the plurality of stakeholders and governance models involved in NbS implementation (47,(80)(81)(82). Although the NbS types identified from our cases do not discriminate governance models because the interview guideline did not target this aspect, we identified that transformative NbS implemented in multi-scale co-production are co-designed with a large range of stakeholders and are coordinated by one of them without necessarily more power (83,84).…”
Section: Discussionsupporting
confidence: 87%
“…In other words, different local contexts can achieve transformative adaptation to one climatic hazard. These findings align with the latest interdisciplinary studies reporting the plurality of stakeholders and governance models involved in NbS implementation (47,(80)(81)(82). Although the NbS types identified from our cases do not discriminate governance models because the interview guideline did not target this aspect, we identified that transformative NbS implemented in multi-scale co-production are co-designed with a large range of stakeholders and are coordinated by one of them without necessarily more power (83,84).…”
Section: Discussionsupporting
confidence: 87%
“…This suggests, in line with NbS global standards [106], that NbS interventions should focus on enabling the decision-making context expected to implement the most appropriate NbS for transformative adaptation rather than only focusing on what type of NbS should address a given climatic hazard. These findings align with the latest interdisciplinary studies reporting the plurality of stakeholders and governance models involved in NbS implementation [37,101,107,108]. The NbS types identified from the study cases do not discriminate governance models because the interview guide did not target this aspect.…”
Section: Plos Climatesupporting
confidence: 81%
“…They show how discourses in other provinces, respectively, the national government, shape discourses about local nonhuman actants. Finally, Méndez et. al.…”
Section: Key Themes Across Contributionsmentioning
confidence: 98%
“…The variety of mostly qualitative and mixed methods mainly generate data from interviews and document analysis, followed by survey and secondary data, clearly displaying the pluralist tradition of situation-centred research (Beckmann and Padmanabhan 2009;Poteete et al 2010). Two studies also employ gametheoretic models (Kasymov et al 2022;Méndez et al 2022), and one uses quantitative multilevel network analysis (Hedlund et al 2022). This conceptual network diversity is also in line with the pluralist approach to the ecology of games that currently exists and has been discussed in the review article in this special feature (Kimmich et al 2022), including qualitative approaches (Dutton et al 2012), quantitative network analyses (Mewhirter et al 2018;Berardo and Lubell 2019;Angst et al 2022), the game-theoretic strand of nested (Distefano and D'Alessandro 2021) and connected games (McGinnis 1986; Khachaturyan and Schoengold 2018; Venkateswaran and Gokhale 2019), and the analytic narrative approach (Bates et al 2000;Kimmich 2016), among others.…”
Section: Diverse Paths and Common Groundsmentioning
confidence: 99%
See 1 more Smart Citation